Reasons for seeking treatments for oral health problem in medical primary care clinics: a pilot mixed method study in Kuantan Pahang - Tin , Myo Han; Md Aris, Mohd Aznan; Thuraiappah, D. M; Sulong, Robiatu Adawiah (Academy of Family Physicians of Malaysia, 2014)
Limited oral health personnel who engage mostly in secondary care is one of the challenges for primary and emergency oral hearth care. There has been evidence of seeking treatment for oral hearth problem(OHPs) at medical primary care clinic (MPCCs) in the mobility reports and oral hearth studies since the late 20th century. however, the reasons for seeking treatments at MPCCs is still unclear. METHODS: A pilot study was conducted by applying mixed method approach to explore the reasons of patients with OHPs for seeking treatment in three selected MPCCs in Kuantan - university clicic (Balok) and private clinic (Clinic Ar-Razi)-from April, 2012 to March 2013. A verified questionnaire including open-ebded questions was used to collect quantitative data from 130 patients who voluntarily participated. In-depth-interviews were conducted for 10 cases using guided questions in the quantitative study. A cross analysis between the type of MPCCs and the reasons of participants was done. Interview transcriptions were analysed by matrix analysis. RESULTS: Regarding reasons for seeking treatment at MPCCs, 60% (78/130) of the answers were non-specific. Among the valid answers, the most common reason was easy access to services (51%) followed by referring to and requiring services provided by primary care physicians (PCPs)(31%) and getting emergency treatment (18%). The reasons were significantly different among the three MPPCs. In the qualitative analysis, 8 out 10 patients perceived that OHPs can be treated by PCPs. More understandable reasons such as co-morbility with medical symptoms, familiarity with PCPs and un-familiarity with dentist and dental phobia were confirmed by the qualitative study. CONCLUSION: This study pointed out the role of PCPs in primary and emergency oral health care. coordinated care between PCPs and dentists should be promoted for OHPs.